Black Priestess of Varda - Fennel, Erik; McWilliams, Al, 1916-1993 (Salt Lake City, UT : Project Gutenberg, 2021)
"Black Priestess of Varda" by Erik Fennel is a science fiction novel written in the mid-20th century. The story involves a complex interplay of magic, technology, and alternate realities, with central figures including Eldon Carmichael, who is grappling with the consequences of a life-changing accident, and Krasna, a woman from the mystical world of Varda. The narrative sets the stage for an epic conflict against dark powers led by a witch named Sin, hinted to be a main antagonist throughout the unfolding plot. The opening of "Black Priestess of Varda" presents a dual narrative: Eldon Carmichael, recovering from a traumatic accident that left him disfigured and psychologically scarred, struggles with self-pity as he attempts to write a letter to his love, Margaret. Meanwhile, Margaret is ensnared in a web of intrigue as Victor Schenley, a man entangled in greed and ambition, becomes a threatening presence in her life. As the story unfolds, Eldon's experiment inadvertently opens a portal to Varda, thrusting him into a volatile world filled with danger and dark powers. Upon arriving, he encounters Krasna, who believes him to be a prophesied savior named Elvedon, setting the stage for a clash between their realities and the malignant forces of Sasso that seek to dominate both worlds. The tensions of betrayal, ambition, and the quest for redemption loom large in this tale, leaving readers eager to explore the depths of its unfolding drama. (This is an automatically generated summary.)
Release date is 2021-02-09
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Adventure stories; Man-woman relationships -- Fiction; Life on other planets -- Fiction